Effects of reciprocating motion parameters on lubricating properties of tripod sliding universal joints. Issue 1 (4th February 2014) - Wang, X.F.; Hu, R.F.; Wang, K.S.; Cui, H.R.
Abstract : Purpose: – This paper aims to clarify the effects of the reciprocating motion parameters on the lubricating performance of the tripod sliding universal joint (TSUJ). These parameters mainly include the frequency and amplitude of the reciprocating motion. This work will explain how the film thickness and pressure as well as the temperature vary with the frequency and amplitude of the reciprocating motion in order to improve the lubricating performance of the TSUJ and extend its working life. Design/methodology/approach: – Based on the simplified geometrical model derived from the main mating surfaces, the effects of the frequency and amplitude on the pressure and film thickness as well as the temperature are theoretically investigated. In this work, multi-level method, multilevel multi-integration method and sequential line sweeping method were applied to solving Reynolds equation, the elastic deformation of the bounding surfaces and temperature, respectively. Findings: – The overall film thickness increases with the increase of the amplitude or frequency. The consumed time of the rippled film passing through the contact zone hardly depends on the amplitude or frequency. The variation of the film or temperature lags behind the variation of the entrainment velocity. Increasing amplitude or frequency increases the temperature. The effect of the amplitude or frequency on the pressure focuses mainly on the second pressure peak. Originality/value: – TSUJ is a new-type tripod joint and the obtained results are of great value for its design and application.